Pengelolaan Masjid Kampus Sebagai Pusat Pendidikan Islam dalam Pembentukan Karakter Mahasiswa di Universitas PGRI Madiun - Rosyida Nurul Anwar; Linda Ayu Wardani; Umiatik Vitriana (Universitas Muhammadiyah Jember, 2019)
Nowadays, character education is a necessity for the people of Indonesia, but moral degradation which infects the public even among students. The campus mosque is a strategic quality building forum for the formation of student character. The purpose of this study was to study the management and role of campus mosques in shaping the character of students at the University of PGRI Madiun. This study uses descriptive qualitative research with data collection techniques using observation, interviews, and documentation. The results of the study show the role of the mosque campus in shaping the character of students; the first character is based on character education based on student activities; second is community-based character education; fourth as a means of learning intolerance between fellow mosque users; and strengthening character through campus culture. This research is expected to increase knowledge for educational institutions that support the role of mosques as centers of Islamic education.